Results of the paleostomatological researches - Kocsis S., Gábor (Acta Biologica Szegediensis, 2000)
Hungarian paleostomatology as the part of dental anthropology exists since the middle of the last century, together with the paleodontical research in the world. The name paleostomatology comes from a Hungarian scientist, György Huszár. The article has the following chapters: Introduction (what is paleostomatology, and its importance), First studies in the world, Nomenclature, The bases of Hungarian paleostomatology, Pioneers of paleostomatological studies in Hungary, Era of the study of caries and other fields of Hungarian paleostomatology, and Hungarian paleostomatology today. The most important representatives of the field are Árkövy, Bruszt, Hillebrand, Huszár, Iszlai, M Lenhossék, Schranz, Tóth, and many anthropologists, doctors, dentists and other scientists. The most researched topics are dental morphology and dental caries but the scientists deal with other fields, too, from an anthropological or medical point of view, such as the morphology and pathology of the facial bones, the alveolar changes, the tooth morphology and variations, the developmental anomalies, the dental attrition, the articulation of dentitions, and so on. In the last couple of years the level of methodology have also corresponded to international needs.